Regulating transnational sustainability regimes / Enrico Partiti, Tilburg University. - Partiti, Enrico (Cambridge University Press, 2022)
The book studies emergence and consolidation of voluntary sustainability standards (VSS); private standards defining sustainability-related product features. The book takes stock of their success and their potential in mediating between economic and non-economic concerns of global production. Despite their private and voluntary nature, VSS generate profound consequences for the producers seeking certification, for the consumers purchasing certified products, and for others affected by their standards. VSS are used by public authorities in the EU as a functional complement to public measures regulating global value chains. At this juncture of market proliferation and public use of private regimes, this book studies how public authority can control, coordinate and review VSS. It studies how the regulation of VSS could unfold through substantive and procedural legal requirements in the domain of European Union law and World Trade Organisation law, as well as through the incentives offered by VSS employment in public measures.